ELECTRICAL AND THERMAL CONDUCTIVITY AND PHONON CONTRIBUTION TO THE THERMAL CONDUCTIVITY IN THE BI-IN SYSTEM - Esener, Pinar Ata; Bayram, Umit; Ozturk, Esra; Aksoz, Sezen; Marasli, Necmettin (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2020)
In this study, the contribution of phonon to the thermal conductivity in the In-Bi (Indium-Bismuth) system due to its composition variation was determined from their electrical and thermal conductivity measurements. Because of the common usage of In-Bi system in many technological applications, thermal and electrical conductivity variations with temperature for different compositions of Bi component were measured. Four-Point Probe (FPP) and Linear Heat-Flow (LHF) methods were used for electrical and thermal conductivity measurements respectively. Intermetallic systems' electrical conductivity values were determined between 0.8524 (1/Omega m) x10(6) and 2.8381(1/Omega m) x10(6) and thermal conductivity values were found between 14.50 (W/Km) and 35.93 (W/Km) at the melting temperature. Electron and phonon contributions to the thermal conductivity were calculated by using Wiedemann-Franz Law (WFL) from the measured values. The temperature coefficients values (alpha) of electrical and thermal conductivity were calculated between 0.46-2.54 (K-1) x10(-3) and 1.29-4.34 (K-1) x10(-3) respectively. In order to observe microstructure of the Bi-In intermetallic alloy Scanning Electron Microscopy (SEM) and to determine the composition of the phases in the structures, Energy Dispersive X-Ray Analysis (EDX) were used. Also melting temperatures (349.03 K-387.24 K), enthalpy of fusion (17.97 J/g- 42.37 J/g) and specific heat change (0.159 J/gK-0.372 J/gK) of Bi-In alloy systems were measured by using Differential Scanning Calorimeter (DSC).
Keywords: Microstructure; Electrical properties; Thermal properties; LIQUID SURFACE ENERGIES; INTERFACIAL ENERGY; SOLID-SOLUTION; SN; OXIDE; CU; TEMPERATURE; EQUILIBRIUM; BISMUTH; Thermodynamics; Engineering